Three-year follow-up optical coherence tomography of under-expanded drug-eluting stent in-stent restenosis treated with ABSORB bioresorbable vascular scaffold following ultra-high pressure pre-dilatation. Issue 1 (January 2018) - Liang, Michael; Tan, Huay-Cheem; Low, Adrian F.
Abstract: The management of in-stent restenosis continues to be a common challenge in modern interventional cardiology. Drug-eluting stents have emerged to be an effective treatment following bare-metal stent in-stent restenosis as compared with drug-coated balloon angioplasty and repeat bare-metal stenting. The addition of another metallic layer is however undesirable and may limit further treatment options. In the last few years, everolimus-eluting bioresorbable vascular scaffolds have become available in treating native coronary artery disease with complete hydrolysis into water and carbon dioxide within 3–5 years. To exploit this property, we successfully used it to manage a case of drug-eluting stent in-stent restenosis from a previously under-expanded stent as demonstrated in this case. Small registry series have also recently been published supporting favorable outcomes with this approach. To the best of our knowledge, this case has the longest optical coherence tomography follow-up beyond 3 years. <Learning objective: The dedicated dual-layer OPN NC balloon (Schwager Medica, Winterthur, Switzerland) could be used in the under-expanded metallic stent that is not overcome by conventional non-compliant balloons as demonstrated in our case. The application of bioresorbable vascular scaffold in drug-eluting stent in-stent restenosis has satisfactory medium- to long-term clinical outcome. The 3-year follow-up intracoronary study demonstrated complete tissue coverage of the scaffold. Complete bioresorption of the scaffold, by hydrolysis into carbon dioxide and water, takes approximately 3–5 years, thus avoiding another layer of metallic cage.>